M. S. 760 'Paris' response to atmospheric turbulence - Clarke, B. S. (College of Aeronautics, 1967)
This report describes work carried out at The College of Aeronautics, Cranfield, during the first year of a contract to study the effects of atmospheric turbulence on the M.S.76O % Paris' aircraft. The aircraft was fitted with an instrumentation system capable of recording ten aircraft quantities, the data being stored on magnetic tape. From data recorded during flight tests, transfer functions for symmetric acceleration responses of the aircraft to turbulence may be obtained. Also, transfer functions may be determined for symmetric tailplane loads in turbulence, including the effect of the downwash from the wing elastic modes, and the tailplane elastic dynamic response. The report contains detailed static and dynamic performance figures of the transducers used, and also descriptions of the three flight tests that have taken place so far, together with results obtained from the analysis of Flight 2.